Respon Iman Kristen Terhadap Pluralitas Agama - Yandri Angelica Silaban; Tabita Mutia Tambunan; Surya Ganda Pasaribu; Satia Febrianty Banurea; Bagida Sitopul (Jurnal Silih Asah, 2024)
This journal discusses the Christian faith response to the growing phenomenon of religious pluralism in the contemporary era. Religious pluralism portrays the diversity of religious beliefs in the modern world, presenting new challenges for Christians in articulating and upholding their faith. In this context, the author identifies three common approaches used in responding to religious pluralism. First, the exclusive approach emphasizes that only one religion is true and valid, while other religions are considered false or invalid. Second, the inclusive approach acknowledges relative truth in each religion, appreciating and recognizing the contributions of each religious tradition. Third, the pluralistic approach regards all religions as valid ways to know and reach God, without claiming superiority of one religion over others. Within the context of Christian faith, the author explores relevant theological views and biblical perspectives in responding to religious pluralism. Some Christian theologians assert the exclusivity of Christ, the belief that salvation can only be found through Jesus Christ. However, there are also Christian theologians who propose inclusive and pluralistic views, stating that Christian faith can coexist with an appreciation of truth in other religions. The author concludes that the Christian faith response to religious pluralism can vary depending on individual theological perspectives and cultural contexts. However, it is important to carefully investigate the foundations of Christian faith and integrate theological views with an inclusive and respectful attitude towards other religions. Keywords: Christian faith, religious pluralism, exclusive approach, inclusive approach, pluralistic approach.